상악 제1소구치의 교두각에 따른 전부도재관의 응력분포에 관한 삼차원유한요소법적 연구 - 김원규; 신동국; 송기범; 동진근; Kim Won-Kyu; Shin Dong-Kuk; Song Kie-Bum; Dong Jin-Keun (Taehan Chikwa Poch'ol Hakhoe chi, 2004)
Statement of problem : Clinically, maxillary first premolar has a high risk of fracture. This is thought to be caused by the susceptible figure which the maxillary first premolar has In other words, sharp cusp angles of the premolar is thought to influence this situation. Purpose : This study was to know stress distribution of all-ceramic crown according to the cusp angle. Material and Method : It was manufactured a three dimensional finite element model simplified maxillary first premolar, and then analyzed stress distribution when cusp angle was each $80^{°}$, $90^{°}$, $100^{°}$, $110^{°}$ and $120^{°}$. Results and conclusion : 1. The von Misses stress showed that stress decreases as cusp angle increases in the central groove of the occlusal surface. 2. It showed that maximum principal stress was centered at the region of the central groove of the occlusal surface and a region which the force was inflicted. And also it appeared high on the lingual and buccal side of finish line. 3. The X axis of normal stress was focused in the central groove of the occlusal surface. The Y axis normal stress appeared high in the central groove of the occlusal surface, buccal and lingual side. 4. The Stress near the finish line showed a low value compared with stress in the region of the central groove of the occlusal surface. 5. It shows that the most dangerous angle for tooth fracture was on $80^{°}$ of the cusp angle and low on $120^{°}$ of its.